ECONOMIC ORDER QUANTITY (EOQ) MODEL: WEIBULL AMELIORATING ITEMS WITH CONSTANT DEMAND RATE - Zubairu, Tijjani brahim Zubairu; Gwanda, Yusuf Ibrahim (FUDMA JOURNAL OF SCIENCES, 2024)
In this study, we investigate the behavior of inventory items having the potential of incurring significant increase in their utilities or values while in stock in accordance to the Weibull distribution law. The amelioration of an inventory occurs when it remains in stock but depletes as a result of constant demand rate. The Weibull amelioration function plays the role of depicting the amelioration state of an inventory whereas the constant demand function describes the different possible stages of market demand. We describe the application of simple, yet analytical, approach for successful derivation and analyses of the underlying inventory system. We furthermore, analyze the model while providing, for the model, the necessary but sufficient and optimal replenishment policy. We use numerical results and examples to better illustrate the solution and successfully carryout the sensitivity analysis and the evaluation of the model.